Prognostic influence of chronic inflammation in patients with head and neck cancer based on sex differences - Antwi-Boasiako, Claudia; Dimitstein, Orr; Chehade, Sophia; Farshadi, Fatemeh; Hier, Michael; Mascarella, Marco A.; Mlynarek, Alex; Alaoui-Jamali, Moulay A.; da Silva, Sabrina Daniela (Clinical & experimental metastasis, 2025)
Head and neck cancer (HNC) is the 7th most common cancer globally. Despite a growing interest of the impact of hormone-specific factors on cancer biology, there is limited understanding of whether the inflammatory microenvironment exhibits significant prognostic differences based on the sex of the patients with HNC. This scoping literature review evaluates if the inflammatory microenvironment exhibits significant variations between male and female patients with HNC. By compiling data from 17 datasets involving 4907patients from seven countries, we confirmed a lower incidence of HNC in females compared to males. However, only few publications addressed the specific effects of endogenous and exogenous hormones remodeling the tumor microenvironment and/or genetic predispositions. Considering sex as a biological variable, the association of various immune and blood vascular cell populations within the tumor microenvironment (including T cells, B cells, macrophages, neutrophils, and blood vessels) was validated in relation to disease progression and metastasis using The Cancer Genome Atlas (TCGA) database for head and neck cancer (Firehose Legacy, n = 528 patients). The outcome is that inflammatory factors associated with sex-specific differences influence the prognostic disparities between males and females. Delineating the molecular mechanisms involved is crucial for advancing precision medicine and tailoring treatment strategies to optimize existing therapies, ultimately improving the overall management and outcomes of HNC patients with aggressive disease.